Transformasi Kepemimpinan di Era Digital: Dampaknya terhadap Employee Engagement di Organisasi Modern - Muhammad Sidik; Sumardin, Sumardin; Sabri, Sabri; Rini Elfina (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Leadership transformation in the digital era has become a critical issue in human resource management, particularly in enhancing employee engagement within modern organizations. The rapid advancement of digital technology demands leaders to adapt not only technically but also strategically and emotionally. This study aims to examine the influence of leadership transformation, digital leadership, and modern organizational characteristics on employee engagement. A quantitative research approach was employed, using multiple regression analysis on a sample of 96 respondents working in digitally driven organizational environments. The results reveal that all three independent variables have a significant partial and simultaneous effect on employee engagement, with a determination coefficient (R²) of 99.2%. These findings indicate that employee engagement can be significantly enhanced through visionary leadership, technological adaptability, and a flexible, innovation-oriented organizational structure. The study concludes that leadership practices and organizational design aligned with digital transformation play a vital role in fostering strong employee involvement. This research contributes both theoretically and practically to the development of organizational management in the digital age.